2017
DOI: 10.1177/0300060516683877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic factors to inhaled corticosteroid response in children with asthma: a literature review

Abstract: Numerous studies have examined the association between pharmacogenetic effects and the response to inhaled corticosteroids (ICS) in patients with asthma. In fact, several single nucleotide polymorphisms of a number of candidate genes have been identified that might influence the clinical response to ICS in children with asthma. Their direct or indirect effects depend on their role in the inflammatory process in asthma or the anti-inflammatory action of corticosteroids, respectively. Among the genes identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…Even though the reason behind childhood asthma is not known, concurrent research showed a combination of environmental contacts and inherited biological, genetic talents [ 6 ]. Pulmonary contacts of its environmental causes are inhaled allergens, viral respiratory infections and chemical contaminants, viral respiratory infections and chemical and biological air pollutants like tobacco smoke in the environment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the reason behind childhood asthma is not known, concurrent research showed a combination of environmental contacts and inherited biological, genetic talents [ 6 ]. Pulmonary contacts of its environmental causes are inhaled allergens, viral respiratory infections and chemical contaminants, viral respiratory infections and chemical and biological air pollutants like tobacco smoke in the environment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a multifactorial disease, which means that both genetic and environmental factors contribute to its development. In fact, genetic factors affect the responses to anti‐asthma drugs in about 60%‐80% of individuals . Currently, complete understanding of the asthma genetics and related pathologic processes has not yet been achieved; therefore, the existing system of diagnosis and treatment of asthma needs further development.…”
Section: Discussionmentioning
confidence: 99%
“…The low‐affinity IgE receptor, CD23, by nature inhibits IgE production . The FCER2 gene affects the inflammatory mechanisms and results in the variability in the response to ICS in asthma . The T2206C variant is located in splicing region of intron 9 of FCER2 and might lead to alternative splicing and changes of the gene transcript length.…”
Section: Discussionmentioning
confidence: 99%
“…gene affects the inflammatory mechanisms and results in the variability in the response to ICS in asthma. 35 The T2206C variant is located in splicing region of intron 9 of FCER2 and might lead to alternative splicing and changes of the gene transcript length. Tantisira et al showed that the T2206C variant was associated with lower FCER2 gene expression.…”
Section: Discussionmentioning
confidence: 99%